(untitled) (Mustansiria Dental Journal, 2025)
Aim: to compare the marginal fitness of zirconia crowns made using laboratory scanners and various cone beam computed tomography (CBCT) parameter.Methods: An extracted premolar tooth was prepared for a crown by zirconia crown preparation criteria. The scanning of the prepared tooth using Medit T710 extraoral scanner (group A), and CBCT scans were made with (planmeca promax) CBCT at different setting parameters: (group B) with the field of view 80x50mm and 150um voxel size and (group C) in which tooth scanned by another CBCT parameters with a field of view 50x50 mm and 75um voxel size. The 3D pictures from the CBCT scans and laboratory scanner were then imported into Exocad software, and a crown design was finished. The crowns are milled from computer-aided design/computer-aided manufacturing CAD/CAM zirconia by a 5-axis milling machine. A stereo-zoom microscope was used to assess the vertical marginal gap. A total of 120 points were measured throughout three groups (4 sites per crown). Vertical marginal gap mean values were obtained by averaging the readings for each specimen. The data was analysed using one-way ANOVA, and the Post hoc Tukey’s test was performed to compare the significance of the difference between groups.Result: one-way ANOVA indicated that there was a significant difference in marginal gaps among the experimented groups (p-value = 0.001). The results of the Post hoc HSD Tukey’s test showed that there was no significant difference between the laboratory scanner (group A) and CBCT scan (group C) with the field of view (FOV) 50x50mm and 75um voxel size (p value=0.052). However, there was a significant difference between the laboratory scanner and CBCT scan group with (FOV) 80x50mm and 150um voxel size (group B), and also between CBCT scan groups (B and C) with different parameters(p-value=0.001).Conclusion: Crowns made with the laboratory scanner exhibited smaller marginal gaps than crowns made using CBCT images with various settings parameters. All three groups were able to fabricate monolithic zirconia crowns with a marginal gap of less than 120um.